Mothers' accounts of mealtime and feeding challenges for children with Tourette syndrome or persistent tic disorders - Bamigbade, Sandra-Eve; Rogers, Samantha L.; Wills, Wendy; Ludlow, Amanda K. (Frontiers in Psychiatry, 2022)
Parenting a young person with a tic disorder can present daily challenges to families struggling to manage their child’s tics and establish routines. Research recognises that tics can be problematic to everyday activities, however no attention has been given to mealtimes, arguably an important family activity closely related to quality of life of the family. The current qualitative study aimed to investigate the mealtime experiences of families with a child with a tic dis-order from the perspective of mothers, looking at mealtime challenges, their impact and how these challenges are navigated. Seventeen mothers with children diagnosed with Tourette Syndrome (TS) or a Persistent Tic Disorder (PTD) (aged 3-14) took part in semi-structured interviews. Interpretative phenomenological analysis of 17 semi-structured interviews resulted in seven subthemes which were grouped under two superordinate themes: (1) tics as a barrier to positive mealtime experiences and (2) eating behaviours and other mealtime challenges. The findings highlight tics to create functional mealtime challenges, affecting a young person’s ability to eat, drink and be seated, with mothers noting the family dynamic was often intensified and compounded by additional challenges related to their child’s tics and comorbidities. Tics also have the power to disrupt the conviviality of mealtimes. For example, eating out-of-home can be especially challenging, with restaurants being high-pressure environments for young people with tics and their families. The cumulative effect of dissatisfaction, stress and additional foodwork can have a diminishing effect on maternal and familial resilience and wellbeing. Mealtime-related interventions need to be considered to help increase confidence and skills in managing mealtimes.